Occupational Health and Safety Risk Assessment of Surabaya Pump Houses using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) Method - Akbar, Reza Aulia; Anityasari, Maria; Arriyanto, Renaldi Jafras; Melchior, Ignatius Dixon; Septaprasetya, Andi Candra; Santoso, Tri Broto (JMES The International Journal of Mechanical Engineering and Sciences, 2025)
Anticipating the impact of heavy rain triggered by climate change, almost all cities in Indonesia have built pump houses to suck up rainwater and puddles on city streets. The performance of the pump to drain and prevent flooding is very important for the people in the city. Unfortunately, not enough attention has been given to ensuring the health and safety of workers in pump houses. The welfare of pump house workers tends to be neglected because the seasonal nature of rain always makes the health and safety of workers in pump houses not a priority. In fact, improving the health and safety of pump house workers will increase the readiness of pump houses to be operated on time when needed. This paper describes the application of the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method commonly used in manufacturing companies to identify, evaluate, and mitigate risks related to the health and safety of workers in pump houses. Samples were taken from 4 different pump houses in Surabaya City, which can then be applied to 61 other pump houses. The results of the study indicate that several actions must be taken immediately to ensure the health and safety of workers. The findings presented in this paper will be useful for other cities in Indonesia to improve the safety culture in the country.